Use of Learning Video Media to Improve Student Learning Outcomes of Grade 5 Elementary School Thematic Online Learning - Danu Dharmoyo (Universitas Sebelas Maret, 2020)
The purpose of this study was to improve student learning outcomes in thematic learning in grade V SD. This research is a classroom action research (PTK) which is carried out in three cycles, each cycle consisting of planning, implementation, observation, and reflection stages. The subjects of this study were 10 grade students of SDN 2 Dlepih in the 2019/2020 academic year. Data collection techniques using observation and tests. Data analysis includes data reduction, data presentation, and drawing conclusions. Research shows that the use of instructional video media can improve student learning outcomes in the subject matter of Theme 3 Sub Theme 2 Learning 2 in class V SDN 2 Dlepih Tirtomoyo in the academic year 2020/2021 as evidenced by the percentage of completeness of learning outcomes in cycle I of 70% to 90% in cycle II and become 100% in cycle III.